Return Of The Mentor : Strategies For Workplace Learning. - Caldwell, Brian (Education policy perspectives., 1993)
A book on the good practise of mentoring which considers the roles of the mentor-mentee in changing workplaces affected by external forces including technology, the economy and the dismantling of middle- management structures and offers guidelines for those who seek good practise.